2012
DOI: 10.1258/ar.2012.120184
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of MR findings in characterizing peroneal tendons disorders in comparison with surgery

Abstract: MRI findings of chronic peroneal tendon pathology are diagnostically specific but not sensitive. MRI showed high sensitivity for diagnosing tendon swelling in the peroneus longus, but not in the peroneus brevis. MRI is sensitive but not specific for detecting negative findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 20 publications
3
26
1
1
Order By: Relevance
“…These results are comparable to the Park et al 32 MRI study on 82 patients, in which 14 peroneal tendon tears were identified preoperatively, and 11 were confirmed during surgery, with a sensitivity of 54.5%, specificity of 88.7%, and accuracy of 84.1%. The Park et al 33 MRI study on 97 patients with chronic lateral ankle pain concluded that MRI is specific but not sensitive in diagnosing peroneal tendon pathology, also confirmed by our results.…”
Section: Discussionsupporting
confidence: 90%
“…These results are comparable to the Park et al 32 MRI study on 82 patients, in which 14 peroneal tendon tears were identified preoperatively, and 11 were confirmed during surgery, with a sensitivity of 54.5%, specificity of 88.7%, and accuracy of 84.1%. The Park et al 33 MRI study on 97 patients with chronic lateral ankle pain concluded that MRI is specific but not sensitive in diagnosing peroneal tendon pathology, also confirmed by our results.…”
Section: Discussionsupporting
confidence: 90%
“…MRI remains a sensitive, but not specific, tool for the diagnosis of peroneal tendon pathologies because of the potential for magic angle artifact from the curvature of the peroneal tendons and difficulties encountered when imaging the tendons out of plane. 4,24,25,27,[29][30][31][32] Quantifiable and reliable techniques are needed for earlier clinical diagnosis of peroneal tendon health to support subjective visual interpretation of the images. Recently, quantitative MRI mapping has been applied to the assessment of tendon and ligament tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Significant fluid collection was defined as the presence of circumferential fluid within the common peroneal tendon sheath with a maximal width greater than 3 mm (11). If the tendon showed clefts and defects that extended into the substance of the tendon itself, a tendon split was diagnosed (12).
Fig.
…”
Section: Methodsmentioning
confidence: 99%